Prevalence of awareness, attitude, and practice towards tobacco use among general public in Kuantan - Al-Shami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Fata Nahas, Abdul Rahman; Elkalmi, Ramadan Mohamed Mahmod; Elsayed, Tarek Mohamed Ali; Akkawi, Muhammad Eid (2020)
Objective: This study aimed to estimate the prevalence of tobacco use among Kuantan communities. The main objective was to study the prevalence, the awareness of , and to assess the attitude and practice of people in Kuantan towards tobacco use. Method: This is a cross-sectional study design. A pre-tested, structured, self-administered research instrument was administered to convenience sample in Kuantan from October to December 2018. A pilot study was prior conducted to establish reliability of research instrument. Data was analysed by (SPSS) software using descriptive as well as inferential analysis. Results: A total of 202 respondents were finally included. The prevalence of tobacco use among Kuantan community is 43.6% with 98.2% in males. Most of the people in the community have high awareness about tobacco use with highest scores being achieved by males and those between 38 to 47 years old. Majority of the Kuantan community demonstrated positive attitude towards tobacco use particularly among females and within the age group of 38 to 47 years old. In terms of practice, majority reported poor practice especially female respondents and those who are under 18-27 age group category. Conclusion: The prevalence of tobacco use in Kuantan community is considered less than half of the total respondents. Most of the people in Kuantan have good awareness, good attitude and poor practice towards tobacco use.